The Analysis Study of Association of Myopia and Age-Related Cataract : A Comprehensive Systematic Review - Anindi Putri Harjanti; Diana Putri (International Medical Journal Corp. Ltd, 2024)
Background: Myopia is a refractive error characterized by the inability to focus on distant objects due to an elongated axial length of the eye. Several studies have suggested that myopia, especially high myopia, may be a risk factor for early-onset cataracts. This systematic review aims to evaluate the association between myopia and age-related cataracts based on literatures of the last decade. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: High myopia increases the risk of cataracts, particularly nuclear and posterior subcapsular types. Age, gender, lifestyle, and myopia severity contribute to cataract formation, highlighting a multifactorial pathogenesis. These findings emphasize the need for targeted prevention and tailored clinical management in myopic patients.